Respuesta :
Let they be
- A(a,a)
- B(-a,-a)
- C(-√3a,√3a)
Find distances
[tex]\\ \rm\Rrightarrow AB=\sqrt{(a+a)^2+(a+a)^2}=\sqrt{4a^2+4a^2}=\sqrt{8a^2}=2\sqrt{2}a[/tex]
[tex]\\ \rm\Rrightarrow BC=\sqrt{(-√3a+a)^2+(√3a+a)^2}[/tex]
- (a+b)^2+(a-b)^2=2a²+2b²
[tex]\\ \rm\Rrightarrow BC=\sqrt{2(\sqrt{3}a)^2+2a^2}=\sqrt{6a^2+2a^2}=\sqrt{8a^2}=2\sqrt{2}a[/tex]
[tex]\\ \rm\Rrightarrow AC=\sqrt{(a+\sqrt{3}a)^2+(a-\sqrt{3}a)^2}=2\sqrt{2}a[/tex]
As
- AB=AC=BC
The traingle is equilateral
Area
[tex]\\ \rm\Rrightarrow \dfrac{\sqrt{3}}{4}a^2[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{\sqrt{3}}{4}(2\sqrt{2}a)^2[/tex]
[tex]\\ \rm\Rrightarrow \dfrac{\sqrt{3}}{4}(8a^2)[/tex]
[tex]\\ \rm\Rrightarrow 2\sqrt{3}a^2[/tex]
[tex] {\large{\textsf{\textbf{\underline{\underline{Solution \: :}}}}}}[/tex]
Let, the given points be
[tex]\bullet \: \tt A (a, a)[/tex]
[tex]\bullet \: \tt B (-a, -a)[/tex]
[tex]\bullet \: \tt C ( - \sqrt{3}a , \sqrt{3}a)[/tex]
Now,
Finding the distances of AB, BC and CD using distance formula.
[tex]\star \: \bold{\underline \red{\sf{ Finding \: AB }}}[/tex]
Using,
[tex] \tt Distance \: Formula = \sqrt{{(x{\small_{2}} -x{\small_{1}} )}^{2} +{(y{\small_{2}} -y{\small_{1}} )}^{2}}[/tex]
where
[tex]\sf x{\small_{2}} = - a[/tex]
[tex]\sf x{\small_{1}} = a[/tex]
[tex]\sf y{\small_{2}} = - a[/tex]
[tex]\sf y{\small_{1}} = a[/tex]
Putting the values,
[tex]\longrightarrow \sf AB = \sqrt{( { - a - a)}^{2} + {( - a - a)}^{2} }[/tex]
[tex]\longrightarrow \sf AB = \sqrt{( { - 2 a)}^{2} + {( -2 a)}^{2} }[/tex]
[tex]\longrightarrow \sf AB = \sqrt{4{ a}^{2} + 4{ a}^{2} }[/tex]
[tex]\longrightarrow \sf AB = \sqrt{8{ a}^{2} }[/tex]
[tex]\longrightarrow \sf AB = \sqrt{2 \times 2 \times 2 \: { a}^{2} }[/tex]
[tex]\longrightarrow \sf AB = \red{2 \sqrt{ 2 }a}[/tex]
[tex] \star \: \bold{\underline \green{\sf{ Finding \: BC }}}[/tex]
Using,
[tex] \tt Distance \: Formula = \sqrt{{(x{\small_{2}} -x{\small_{1}} )}^{2} +{(y{\small_{2}} -y{\small_{1}} )}^{2}}[/tex]
where
[tex]\sf x{\small_{2}} = - \sqrt{3}a [/tex]
[tex]\sf x{\small_{1}} = - a[/tex]
[tex]\sf y{\small_{2}} = \sqrt{3}a [/tex]
[tex]\sf y{\small_{1}} = - a[/tex]
Putting the values,
[tex] \longrightarrow \sf BC = \sqrt{ \bigg[ { - \sqrt{3}a - (- a) \bigg]}^{2} + {\bigg[ \sqrt{3}a - (- a)\bigg]}^{2} }[/tex]
[tex] \longrightarrow \sf BC = \sqrt{ { ( - \sqrt{3}a + a) }^{2} + {( \sqrt{3} a + a)}^{2} }[/tex]
Using (a + b)² = a² + 2(a)(b) + b².
[tex]\longrightarrow \sf BC = \sqrt{ { (- \sqrt{3}a) }^{2} + 2( - \sqrt{3} a)(a) + {(a)}^{2} + {( \sqrt{3} a + a)}^{2} }[/tex]
[tex]\longrightarrow \sf BC = \sqrt{ 3 {a}^{2} - 2 \sqrt{3} {a}^{2} + {a}^{2} + {( \sqrt{3} a + a)}^{2} }[/tex]
Again, using (a + b)² = a² + 2(a)(b) + b².
[tex]\longrightarrow \sf BC = \sqrt{ 3 {a}^{2} - 2 \sqrt{3} {a}^{2} + {a}^{2} + { ( \sqrt{3}a) }^{2} + 2( \sqrt{3} a)(a) + {(a)}^{2} }[/tex]
[tex]\longrightarrow \sf BC = \sqrt{ 3 {a}^{2} \:\cancel{ - 2 \sqrt{3} {a}^{2}} + {a}^{2} + 3 {a}^{2} \:\cancel{ + 2 \sqrt{3} {a}^{2}} + {a}^{2} }[/tex]
[tex] \longrightarrow \sf BC = \sqrt{ 3 {a}^{2} + {a}^{2} + 3 {a}^{2} + {a}^{2} }[/tex]
[tex] \longrightarrow \sf BC = \sqrt{ 8 {a}^{2} }[/tex]
[tex]\longrightarrow \sf BC = \sqrt{2 \times 2 \times 2 \: { a}^{2} }[/tex]
[tex] \longrightarrow \sf BC = \green{2 \sqrt{ 2 }a}[/tex]
[tex] \star \: \bold{\underline \orange{\sf{ Finding \: AC }}}[/tex]
Using,
[tex] \tt Distance \: Formula = \sqrt{{(x{\small_{2}} -x{\small_{1}} )}^{2} +{(y{\small_{2}} -y{\small_{1}} )}^{2}}[/tex]
where
[tex]\sf x{\small_{2}} = - \sqrt{3}a [/tex]
[tex]\sf x{\small_{1}} = a[/tex]
[tex]\sf y{\small_{2}} = \sqrt{3}a [/tex]
[tex]\sf y{\small_{1}} = a[/tex]
Putting the values,
[tex] \longrightarrow \sf AC = \sqrt{ { ( - \sqrt{3}a - a)}^{2} + {(\sqrt{3}a - a)}^{2} }[/tex]
Using (a - b)² = a² - 2(a)(b) + b².
[tex] \longrightarrow \sf AC = \sqrt{ {( - \sqrt{3} a)}^{2} - 2( - \sqrt{3} a)(a) + {(a)}^{2} + {(\sqrt{3}a - a)}^{2} }[/tex]
[tex] \longrightarrow \sf AC = \sqrt{ 3 {a}^{2} + 2 \sqrt{3} {a}^{2} + {a}^{2} + {(\sqrt{3}a - a)}^{2} }[/tex]
Again, using (a - b)² = a² - 2(a)(b) + b².
[tex]\longrightarrow \sf AC = \sqrt{ 3 {a}^{2} + 2 \sqrt{3} {a}^{2} + {a}^{2} + {( \sqrt{3} a)}^{2} - 2( \sqrt{3}a)(a) + {(a)}^{2} }[/tex]
[tex]\longrightarrow \sf AC = \sqrt{ 3 {a}^{2} \: \cancel{ + 2 \sqrt{3} {a}^{2} } + {a}^{2} + 3 {a}^{2} \: \cancel{ - 2 \sqrt{3} {a}^{2} } + {a}^{2} }[/tex]
[tex]\longrightarrow \sf AC = \sqrt{ 3 {a}^{2} + {a}^{2} + 3 {a}^{2} + {a}^{2} }[/tex]
[tex]\longrightarrow \sf AC = \sqrt{ 8 {a}^{2} }[/tex]
[tex] \longrightarrow \sf AC = \sqrt{2 \times 2 \times 2 \: { a}^{2} }[/tex]
[tex] \longrightarrow \sf AC = \sqrt{2 \times 2 \times 2 \: { a}^{2} }[/tex]
[tex]\longrightarrow \sf AC = \orange{{2\sqrt{2 }}a}[/tex]
Since,
AB = BC = CA = [tex] \sf {{2\sqrt{2 }}a} [/tex]
Therefore, the [tex]\triangle [/tex] ABC formed by the given points is an equilateral triangle.
For,
Finding the area of [tex]\triangle [/tex] ABC
Using,
[tex]\longrightarrow \: \tt Area_{(equilateral \: \triangle)} = \dfrac{ \sqrt{3} }{4} \: {(side)}^{2} [/tex]
Putting,
• side = [tex] \sf {{2\sqrt{2 }}a} [/tex]
[tex]\longrightarrow \: \tt Area_{(equilateral \: \triangle)} = \dfrac{ \sqrt{3} }{4} \: {(2 \sqrt{2}a )}^{2} [/tex]
[tex]\longrightarrow \: \tt Area_{(equilateral \: \triangle)} = \dfrac{ \sqrt{3} }{4 } \times 2 \times 2 \times 2 \times {a}^{2} [/tex]
[tex]\longrightarrow \: \tt Area_{(equilateral \: \triangle)} = \dfrac{ \sqrt{3} }{ \cancel{4}} \times \cancel{8 }{a}^{2} [/tex]
[tex]\longrightarrow \: \tt Area_{(equilateral \: \triangle)} = \purple{2 \sqrt{3} {a}^{2} \: sq. \: units}[/tex]
[tex]\therefore \sf Area = 2 \sqrt{3} {a}^{2} \: sq. \: units[/tex]
[tex] {\underline{\rule{310pt}{2pt}}} [/tex]
![Ver imagen ItzBrainlyCommando](https://us-static.z-dn.net/files/d72/61c7e9aeb089f277dc9fde9085a219cb.jpg)